2003
DOI: 10.5713/ajas.2003.1583
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Retention and Chemical Composition of Urea Treated Wheat Straw Ensiled with Organic Acids or Fermentable Carbohydrates

Abstract: The influence of varying levels of urea and additives on nitrogen (N) retention and chemical composition of wheat straw was studied. The wheat straw was treated with 4, 6 and 8% urea and ensiled with 1.5, 2 and 2.5% of acetic or formic acid and 2, 4 and 6% of corn steep liquor (CSL) or acidified molasses for 15 days. The N content of wheat straw was significantly different across all treatments. The N content of urea treated wheat straw was increased with the increasing level of urea. The N content was higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 38 publications
1
24
1
Order By: Relevance
“…Furthermore, N can be recycled by ruminants to compensate for differences in the release time of N in the rumen (Reynolds & Kristensen, 2008;Toprak et al, 2016). It is now well established that N retention depends on the intake of N and the amount of fermentable carbohydrate in the diet (Sarwar et al, 2003). However, Sherwood et al (2006) found that N mass balance was not affected by the addition of zeolite clay in steers fed with 12 g zeolite per kg.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, N can be recycled by ruminants to compensate for differences in the release time of N in the rumen (Reynolds & Kristensen, 2008;Toprak et al, 2016). It is now well established that N retention depends on the intake of N and the amount of fermentable carbohydrate in the diet (Sarwar et al, 2003). However, Sherwood et al (2006) found that N mass balance was not affected by the addition of zeolite clay in steers fed with 12 g zeolite per kg.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, nitrogen retention was decreased. It is now well established that nitrogen retention depends on the intake of nitrogen and the amount of fermentable carbohydrates in the diet [ 28 ]. However, the positive nitrogen balance observed in this study indicated that the positive combination of FTOPF in the TMR was based on feeding of goats.…”
Section: Discussionmentioning
confidence: 99%
“…Higher proportion of A and B 1 fractions of N in these diets also substantiates our results. Sarwar et al (2003) reported that the rumen micro-organisms built their protein from both amino acid and ammonia arising from NPN of the food (McDonald et al, 2003), and 80% of the main source of nitrogen for ruminant micro-organism is ammonia (Chalupa and Sniffen, 1996). Increased EE digestibility in CUF group is in agreement with our earlier results (Bhatt et al, 2013b) and is due to higher digestion of fatty acids in calcium soap owing to the lower ruminal biohydrogenation and subsequently higher levels of unsaturated fatty acids in intestinal chyme (Wu et al, 1993).…”
Section: Digestibility Of Nutrients Balance Of Nitrogen Calcium Andmentioning
confidence: 99%